Under-13 rugby: What are the issues? A panel discussion - Durandt, Justin; Hendricks, Sharief; Marshall, Mike; Roux, Andries; Hare, Eugene (South African Journal of Sports Medicine, 2015)
There are many questions about youth rugby for which there are no immediate answers. At what age should the young players specialise? How often should they practise? How many matches should they play in season? Science has lagged behind in providing clear answers, and in many cases decisions about the development of the game at this level have to be made based on logic and intuition. As a result, opinions may differ and controversy may prevail. Recently a panel of experts representing different aspects of youth rugby was asked a series of questions about this sport, the aim being to examine the answers given from different perspectives. The overall goal was to identify where agreement does or does not exist.